Pengaruh Penggunaan Abu Kayu Sebagai Material Penutup TPA Terhadap Kosentrasi TSS, TDS dan Pb dalam Air Lindi Sampah - Aritonang, Bonardo Agustinus; Amelia, Vera; Widiastuti, Lusia (Universitas Pahlawan Tuanku Tambusai, 2024)
Law Number 18 of 2008 concerning Waste Management requires the closure of landfills with an open dumping system and replacing them with a sanitary landfill system, thus requiring a fairly large landfill cover layer. On the other hand, the amount of wood ashes produced in Indonesia is very abundant and has been widely used as an adsorbent and pozzolan material. Wood ashes has the potential to be used as a landfill cover material based on sanitary landfills, especially daily cover and intermediate cover. This research has purpose to analyze the differences in surface area and silica content contained in laterite soil and wood ashes, analyze differences in the volume of leachate produced from the use of wood ashes and laterite soil as a landfill cover layer, analyze the effect and whether the use of wood ashes as a cover layer material TPA produces better quality TSS (total suspended solid), TDS (total dissolved solid), and Pb (lead) than using laterite soil. This research was carried out by using 3 lysimeters, that is a lysimeter without a covered layer, a lysimeter with a laterite covered layer, and a lysimeter with a wood ash covered layer. The results of the research show that the surface area of wood ashes and laterite soil has a similar surface area, but the Si content in wood ashes is higher than in laterite soil. The lysimeter with a covering layer of wood ash produces a smaller volume of leachate than the volume of leachate from other lysimeter variants, lysimeters with wood ashes cover layers have a negative effect on TDS concentrations so they will produce higher TDS concentrations compared to lysimeters that use laterite soil cover layers and have a positive effect on TSS and Pb concentrations so they will produce TSS concentrations and lower Pb compared to lysimeters that use a laterite soil cover layer. Lysimeter with a laterite cover layer have a negative effect on the TSS concentration of leachate so that they will produce a higher TSS concentration compared to the TSS cocentration of leachate from lysimeter without a cover layer and lysimeter with a wood ash cover layer.